SOLO MICE HALL DENGAN PENERAPAN ANALOGI PENDHAPA - Danu Kartikasunu; Edi Pramono Singgih; Leny Pramesti (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Many activities and events related to the MICE held in Solo, ranging from local to international scales, both indoors and outdoors. However, the abundance of MICE activities were not followed by the development of MICE facilities in Solo. The MICE’s existing facilities in Solo didn’t accommodated MICE activities so well. Therefore, Solo require a facility that can accommodate a variety of MICE events in Solo. This is the writer’s background to design a Solo MICE Hall’s building with various supporting facilities. Java traditional house also has a part that function as meeting area, that called pendhapa. The problem design is how to applying pendhapa’s philosophical essence in Solo MICE Hall’s building. The method used is application of analogy architecure to the design. The result is the design of the MICE facilities in Solo with applying pendhapa’s philosophical essence using analogy method, so this building is expected to have a value of Javanese building summarized in a design Solo MICE Hall. Keywords: Pendhapa, MICE, Analogy of Architecure